Screening of Cowpea (Vigna unguiculata (L). Walp) Genotypes for Resistance to Yellow Mosaic Disease Caused by CYMV and BCMV using Specific SSR Markers - Nagesha, N.; Pramod, S. A.; Krishna, T. V.; Kanavi, M. S. P.; Lakshminarayana Reddy, C. N. (International Journal of Bio-resource and Stress Management, 2024)
The research was conducted during August to November, 2020 at the Department of Plant Biotechnology and Dryland Farming Unit, University of Agricultural Sciences (UAS), Gandhi Krishi Vigyana Kendra (GKVK), Bengaluru, Karnataka, India to validate the identified SSR markers associated with resistance to yellow mosaic diseases of cowpea using different genotypes. 120 germplasm lines cowpea were used for the study including two check varieties (IC-202781 and V-585). Disease scoring scale by Diwakar and Mali (1976) was used for the disease scoring. Among 120 genotypes, 52 genotypes with moderately resistance, 28 genotypes with no disease symptoms, 15 genotypes with resistance, 14 genotypes with moderately susceptible, 11 genotypes with susceptible and no highly susceptible genotypes were observed. These germplasms were screened using four simple sequences repeat markers (SSR) specific to Bean common mosaic virus and four SSR markers specific to cowpea yellow mosaic virus were selected from the existing databases. Out of the four SSR marker linked to BCMV tested for validation, only three markers (M15, M80, and Y 96) gave the desired amplification. Single marker analysis (SMA) revealed that out of four SSR markers, MA15 marker explains 3.96% of phenotypic variation, among 4 SSR markers linked to CYMV, only two markers (VM1 and AG1/AF48383) gave the desired amplification. SMA revealed that out of two SSR markers, AG1/AF48383 marker explains 3.80% of phenotypic variation. The resistant genotypes identified in this investigation can be used in future breeding programmes for introgression of disease resistant traits in important competitive varieties in the market.